2022
DOI: 10.3390/agriculture12040462
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Use, Soil Health and Agricultural Sustainability

Abstract: Due to the growing population and consequent pressure of use, agricultural soils must maintain adequate levels of quantity and quality to produce food, fiber, and energy, without falling victim to a negative impact on their balance of nutrients, health, or their ability to function [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(50 citation statements)
references
References 21 publications
0
50
0
Order By: Relevance
“…The fertilizer effects of both inorganic and organic fertilizer as well as their combination were significant on plant height, where the unfertilized treatment was shorter than other treatments. That is showing the fertilizers need in agricultural production [4,6,7]. Since the plant starting harvested in 90-100 dap, the measurement of products accumulated in 120dap as well as determining the survival productive plants.…”
Section: Resultsmentioning
confidence: 99%
“…The fertilizer effects of both inorganic and organic fertilizer as well as their combination were significant on plant height, where the unfertilized treatment was shorter than other treatments. That is showing the fertilizers need in agricultural production [4,6,7]. Since the plant starting harvested in 90-100 dap, the measurement of products accumulated in 120dap as well as determining the survival productive plants.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of quantum of FYM drives a sole factor for nutrient cycling and nutrient transformation in soil. Theses effective catalyst may induce the proper microbial growth and nutrient availability for plant growth by increasing the SOC [19,20]. Other plots which received recommended dose of nutrients such as T 2 to T 5 and T 7 plots are on par with each other and the lowest in control plot of 4.2 g kg -1 SOC in maize crop.…”
Section: Soil Organic Carbon (G Kgmentioning
confidence: 99%
“…Thus, the type of nutrient source, nutrient content in the soil, nutrient content in the crop/animal and these wastes relate to one another. [18] reported that the differences in yields and soil properties are explained by the nature of the organic waste products used. The use of modern inputs impacted the output values in terms of nutrient contents availability within crops/pastures that were later reflected in the farm wastes as baseline nutrients.…”
Section: And Environmentmentioning
confidence: 99%